Effect of the Substitution of the Mesityl Group with Other Bulky Substituents on the Luminescence Performance of [Pt(1,3-bis(4-Mesityl-pyridin-2-yl)-4,6-difluoro-benzene)Cl] - Giulia De Soricellis; Véronique Guerchais; Alessia Colombo; Claudia Dragonetti; Francesco Fagnani; Dominique Roberto; Daniele Marinotto (Molecules)
The synthesis and characterization of two new complexes, namely [Pt(bis(4-(4-(tert-butyl)phenyl)-pyridin-2-yl)-4,6-difluorobenzene)Cl] and [Pt(bis(4-(3,5-di-tert-butylphenyl)-pyridin-2-yl)-4,6-difluorobenzene)Cl], are reported. Both are highly luminescent in the blue region (Φlum = 0.89–0.95 at 478–480 nm), like the parent complex [Pt(1,3-bis(4-mesityl-pyridin-2-yl)-4,6-difluoro-benzene)Cl] in degassed diluted dichloromethane solution. An increase in concentration leads to the formation of bi-molecular emissive excited states, as evidenced by a growing structureless band that peaked at 690–697 nm. This formation is more facile for the complex with one tert-butyl group in para of the phenyl group. It appears that the introduction of two tert-butyls in positions 3 and 5 of the phenyl group hampers the neighboring of the monomeric species, although less efficiently than the introduction of methyls in positions 2 and 6.